Pre and postharvest enzymatic activity in gulupa (passiflora edulis sims) fruits from the colombian lower montane rain forest / actividad enzimática precosecha y poscosecha en frutos de gulupa (passiflora edulis sims), en condiciones del bosque húmedo mo (2014)
“High-Andean fruits” are deemed important because oftheir potential for domestic consumption and exportation. Among them, gulupa (Passiflora edulis Sims) is an exotic fruit of good acceptance in European markets. However, the technological support associated with the crop is incipient and its short shelf life leads to rapid deterioration of the product. This fact makes it necessary to investigate the physical, physiological and biochemical processes that characterize fruit ripening, in order to take actions to ensure that it arrives in its best possible condition to the consumer. In this context, the current study aimed at identifying enzymatic activity in gulupa fruits during pre and postharvest. Plant materialfrom the Colombian Gene Bank (administered by Corpoica) was used. Fruits of known age were periodically harvested to determine the activity of the enzymes α-amylase, polygalacturonase (PG), pectinmethylesterase (PME) and polyphenol oxidase (PPO) through destructive samplings. It was found that α-amylase and PG are linked to the increase of soluble solids, which favors the sweet taste of the fruit. In turn, the low activity of PPO enables agroindustrial processing without severe fruit browning. / Los “frutales alto-andinos”, se consideran importantes por su potencial de consumo nacional y exportación. Entre ellos está la gulupa (Passiflora edulis Sims), reconocida como un frutal exótico de buena aceptación en mercados europeos. Sin embargo, el respaldo tecnológico asociado al cultivo, es incipiente y su corta vida poscosecha conduce al rápido deterioro del producto. Esto hace necesario plantear estudios de los procesos físicos, fisiológicos y bioquímicos que caracterizan la maduración, con el fin de procurar que el fruto llegue en las mejores condiciones de calidad a los consumidores. El estudio tuvo como objetivo conocer la actividad enzimática en los frutos de gulupa en precosecha y en poscosecha, con el fin de contribuir a su manejo en estas etapas del desarrollo. Se utilizó material vegetal proveniente del Banco de Germoplasma de la nación Colombiana administrado por Corpoica, haciendo muestreos destructivos periódicos de frutos con edad conocida, para determinar la actividad de las enzimas α-amilasa, poligalacturonasa (PG), pectinmetilesterasa (PME) y polifenoloxidasa (PFO) en la pulpa del fruto. Se encontró que las enzimas α-amilasa y PG, auspician el incremento en la acumulación de sólidos solubles, favoreciendo el sabor dulce del fruto, en tanto que la baja actividad de la enzima PFO, posibilita la transformación agroindustrial, sin que se presente pardeamiento